First-year evaluation of a campus-wide, cross-disciplinary scholarly writing development program supported by a center for biomedical research excellence (COBRE). - Amy M Franks; Benjamin S Teeter; Payton Davis; Mallory Allred; Reid D Landes; Igor Koturbash; Judith Weber (PLoS ONE)
Background Scholarly publications are important indicators of research productivity and investigator development in Centers of Biomedical Research Excellence (COBREs). However, no information is available to describe implementation and evaluation of writing development programs within COBREs. Therefore, this paper aimed to evaluate the first year of a campus-wide COBRE-supported writing program. Methods A convergent parallel mixed-methods design (QUAN + QUAL) was used. All writing program participants were invited to complete post-participation surveys, and a subgroup was selected using purposive sampling to complete individual semi-structured interviews. Descriptive statistics were used to characterize survey data, and qualitative content analysis was employed to analyze interview data. Self-determination theory served as the theoretical framework by which themes were developed and interpreted. Results Professional staff, post-doctoral fellows, and faculty from all academic ranks (n = 29) participated in the writing program during its first year. Survey respondents (n = 18, response rate 62%) rated social support (89%), group accountability (89%), hearing group members' writing goals (78%), receiving group advice (67%), and setting a weekly writing schedule (56%) as beneficial program components. Participants rated program benefits such as breaking away from other responsibilities, staying on task with writing goals, and receiving social support as most beneficial. During interviews, participants (n = 14) described five major themes related to the benefits received: 1) belonging to a community of writers; 2) managing writing-related emotions; 3) improved productivity; 4) establishing helpful writing habits; and 5) improved motivation for scholarly writing. Conclusions This first-year programmatic evaluation demonstrates the writing program's effectiveness as a campus-level development resource supported by a research center. Both survey and interview data affirmed that participants perceived autonomy, competence, and relatedness were supported through participation in the writing program. Participants placed particular emphasis on the writing program's successful development of a community of scholarly writers.